A novel sintering additive system for porous mullite-bonded SiC ceramics: High mechanical performance with controllable pore structure. Issue 3 (1st February 2022) - Li, Zihe; Chang, Zixuan; Liu, Xinran; Zhao, Weimin; Zhang, Xu; Xiao, Shikang; Tian, Yuhang; Li, Aijun; Han, Guifang; Li, Jianzhang; Zhang, Jingde
Abstract: High strength and thermal shock resistant mullite-bonded porous SiC ceramics are essential for applications in catalyst, hot gas/solid filtration/separation fields. However, these properties were limited by the contradictory issue: higher temperature is necessary for the formation and densification of mullite bond phase, while lower temperature is preferred to avoid sever oxidation of SiC accompanied with detrimental cristobalite phase. Herein, a novel composite additive system, Al(OH)3 +Y2 O3 +CaF2, was proposed to solve this problem for one shot. Flexural strength as high as 113 MPa (40.3 vol% porosity) was achieved for samples sintered in air, even higher than that fabricated by expensive SPS technique (103 MPa, 35.7 vol%). Critical quenching temperature reached 547 °C, around 227 °C improved. Meanwhile, additives acted as pore formers and small variation of them could effectively modify the size and shape of pores. The evolution of pore structure with additives was thoroughly evaluated and models were established for the first time. Correlations of phase composition, microstructure, porosity, pore size and shape to the performance of porous SiC were investigated. This work provides a flexible strategy to simultaneously control the mechanical performance and pore structure for low cost porous SiC ceramics. Graphical abstract: Image 1 Highlights: A composite sintering additive system was first proposed for mullite-bonded SiC. Realized phase and pore structure control and in-situ reinforcement simultaneously. Corresponding phase evolution route and pore-forming models were first established. Flexural strength reached 113 MPa sintered in air, higher than those sintered by SPS. Significantly enhanced thermal shock resistance with ΔT c improved from 320 to 547 °C.